Conventional and Molecular Typing of Salmonella enterica serotype Typhi Locally Isolated In Baghdad - Baghdad Science Journal (مجلة بغداد للعلوم)
Phenotypic And genotypic characteristics of Salmonella enterica serotype Typhi have been determined for 29 isolates, from Baghdad in 2007. Conventional typing methods were performed by biochemical tests, and antimicrobial susceptibility test. Molecular typing performed by analysis plasmid DNA beside using the Random Amplified Polymorphic DNA (RAPD-PCR). For the latter, two universal primers that have selected for the high discriminatory power were used for RAPD analysis. All isolates were belong one biotype according to the differention by their ability to decarboxylat lysine, 29(100%) were lysine (+). All the isolates were susceptible to the Antibiotics used. However, all the strains free of plasmids. RAPD was capable of grouping the strains in 6 genotypic patterns using primer 784, in 4 genotypic patterns using primer 787. Conventional phenotypic typing methods, as well as the DNA plasmid analysis, presented non significant discriminatory power; however, RAPD-PCR analysis showed discriminatory power, reproducibility, easy interpretation and can be considered as a promising alternative typing method for S. Typhi.